2012
DOI: 10.1093/jopart/mus004
|View full text |Cite
|
Sign up to set email alerts
|

Does My Boss's Gender Matter? Explaining Job Satisfaction and Employee Turnover in the Public Sector

Abstract: Substantial literatures exist examining public personnel turnover and the role of gender in public management. We bring these two strands of research together to test hypotheses concerning the impact of manager gender on the job satisfaction and turnover of public sector workers. In particular, we test whether manager gender influences satisfaction and turnover per se versus the competing claim that gender congruence between managers and employees, regardless of gender, is the relevant construct. Using data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
217
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(231 citation statements)
references
References 88 publications
11
217
1
2
Order By: Relevance
“…This distinction allows for males to display female gender leadership qualities and vice-versa; still, most studies tend to equate the two and have focused primarily on differences between men and women leaders. Many studies examining gender based differences in leadership use the sex of the principal rather than measures reflecting gender as a social construction (Grissom, Nicholson-Crotty, & Keiser, 2012); this conflation is reflected in the review of relevant literature in the following sections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This distinction allows for males to display female gender leadership qualities and vice-versa; still, most studies tend to equate the two and have focused primarily on differences between men and women leaders. Many studies examining gender based differences in leadership use the sex of the principal rather than measures reflecting gender as a social construction (Grissom, Nicholson-Crotty, & Keiser, 2012); this conflation is reflected in the review of relevant literature in the following sections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Schaffer and Riordan ( 2013 ) found that gender similarity/dissimilarity within the supervisory dyad had no discernible effects on employee ratings of supervisory support, discrimination, or relationship quality. Grissom et al ( 2012 ) found that female teachers were equally satisfi ed, and equally likely to be retained, whether they reported to a female principal or a male one. Male teachers, in contrast, were less satisfi ed and more likely to leave when they were supervised by a female principal.…”
Section: When the Boss Is A Womanmentioning
confidence: 91%
“…doi: 10.14687/ijhs.v11i2.3032 851 various justice types (i.e., interpersonal, informational, procedural, and distributive justice) (e.g., Cole, 2004) and the relationship between employees' gender and sensitivity towards different types of justice (e.g., Buttner, 2004). Although there is some empirical evidence that female supervisors or leaders are perceived as higher on interpersonal justice than their male counterparts by both female and male subordinates, the results are conflicting when findings of studies investigating the effects of gender-match between supervisors and employees on various outcomes such as preference to work with the supervisor and job satisfaction are taken into consideration (e.g., Grissom, Nicholson-Crotty, & Keiser, 2012;Wharton & Baron, 1991). To illustrate, the literature shows that interpersonal and informational justice are strongly associated with positive employee outcomes such as job satisfaction, organizational commitment, and organizational citizenship behavior (Colquitt, Conlon, Wesson, Porter, & Ng, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Still, there are a number of recent studies which found that male employees reported significantly lower levels of job satisfaction and higher level of turnover intentions when they worked with female supervisors (e.g., Grissom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%